Screening of Pesticide Residues in Fresh Vegetables and Fruits by LC-MS/MS and GC-MS/MS - Gurbuz1, N.; Arik2, O.; Baykal1, A. (Asian Journal of Chemistry, 2014)
To determine maximum residue limit of our samples exported from Antalya province of Turkey, we analyzed 3798 samples of fresh vegetables and fruits from 2009-2012 by LC-MS/MS and GC-MS/MS systems for 130 and 16 pesticides, respectively. Additionally, the results were compared based on three different countries' directives. Our findings showed that pesticide residues were detected in 1063 samples (27.98 %). When 1063 samples were analyzed based on different directives, over maximum residue limits were detected in 211 (5.5 %), 118 (3.1 %) and 95 (2.97 %) samples according to the Russian, European Union and Turkish directives, respectively. These samples were mainly tomatoes, cucumbers, bell peppers, lemon and pomegranate. Additionally, acetamiprid, azoxystrobin, carbendazim, imidachlorpid were four of most frequently pesticides detected in our samples when evaluated them based on pesticide type. It is necessary to conduct analysis not only in exported products but also making routine analysis in nationally consumed fruits, vegetables and food products on grocery store shelves.